Head injuries in winter sports: Downhill skiing, snowboarding, sledding, snowmobiling, ice skating and ice hockey - Chaze, B.; McDonald, P. (Physical Medicine & Rehabilitation Clinics of North America, 2009)
Winter sports are often associated with high speed, which carries with it the potential for collision. As such, head injuries are among the more commonly encountered injuries in winter-related sporting activities. This article focuses on popular winter sports such as downhill skiing and snowboarding, sledding, snowmobiling, ice skating, and hockey. In virtually all of these activities, the incidence and severity of head injuries can be reduced by the use of appropriate protective headgear.